Rumah Betang: Tinjauan Historis Arsitektur Tradisional Suku Dayak Siang Di Desa Tumbang Apat Puruk Cahu - Aminah, Siti; Hairiyadi, Hairiyadi; Effendi, Rusdi (Prabayaksa: Journal of History Education, 2021)
The simplicity and unique form of the Betang Tumbang Apat house building has its own meaning, apart from the simplicity of the building, this form directs the Dayak Siang community to individuals who do not see status or caste. This study aims to determine the meaning and characteristics of the traditional architecture of the Dayak Siang Tribe Betang House in Tumbang Apat Village, Sungai Babuat District, Murung Raya Regency. In this research, the writer uses historical method. The first step is to collect related data. The second stage is verifying data and criticizing sources of oral data and object data. Next is the interpretation or interpretation of the data, the facts that have been obtained. The last stage of historiography is writing history based on the facts that have been interpreted. The results showed that the traditional architecture of the Betang house of the Dayak Siang tribe is still preserved and it is conscious that the surrounding community also preserves the culture.